The multiple advantages of minimally invasive orthognatic surgery: A literature review (Research, Society and Development, 2023)
Introduction: Orthognathic surgery is an area of oral and maxillofacial surgery that aims to treat dentofacial disorders. Because it is a therapeutic option that helps correct the relationship between facial dimensions and dental positions, it also contemplates the achievement of functional results, while providing satisfactory facial harmony. Objective: to carry out an integrative literature review on the multiple advantages of minimally invasive orthognathic surgery. Methodology: The searches for scientific evidence were carried out in databases such as: Virtual Health Library, Scientific Electronic Library Online and PubMed using the search terms: Orthognathic Surgery, Dentistry, Maxillofacial Procedures. And so, selected complete and published articles, found in the cited sites. Results: Initially, 45 articles were found. After selection, 10 were suitable for the purposes of the study, the information was transferred to the collection instrument. The included articles were presented in a summary table and the analysis of the results was carried out in a descriptive way, presenting the synthesis of the studies through comparisons and highlighting the differences and/or similarities Conclusion: It is concluded in this review that there is relevance of minimally surgical procedures within orthognathic surgery, since these promote multiple advantages to patients both in the reduction of neurovascular and salivary complications and in the reduction of morbidities resulting from these surgical acts.